Wide sampling of natural diversity identifies novel molecular signatures of C4 - Kelly, Steven; Covshoff, Sarah; Wanchana, Samart; Thakur, Vivek; Quick, W. Paul; Wang, Yu; Ludwig, Martha; Bruskiewich, Richard; Fernie, Alisdair R.; Sage, Rowan F.; Tian, Zhijian; Yan, Zixian; et al. (Cold Spring Harbor Laboratory, 2017)
Much of biology is associated with convergent traits, and it is challenging to determine the extent to which underlying molecular mechanisms are shared across phylogeny. By analyzing plants representing eighteen independent origins of C4photosynthesis, we quantified the extent to which this convergent trait utilises identical molecular mechanisms. We demonstrate that biochemical changes that characterise C4species are recovered by this process, and expand the paradigm by four metabolic pathways not previously associated with C4photosynthesis. Furthermore, we show that expression of many genes that distinguish C3and C4species respond to low CO2, providing molecular evidence that reduction in atmospheric CO2was a driver for C4evolution. Thus the origin and architecture of complex traits can be derived from transcriptome comparisons across natural diversity.